2016
DOI: 10.1371/journal.pone.0147915
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Reduction Is Associated with Reduced Venous Pulsation Pressure

Abstract: PurposeTo explore whether alterations in intraocular pressure (IOP) affect vein pulsation properties using ophthalmodynamometric measures of vein pulsation pressure.Patients and MethodsGlaucoma patients had two retinal vein pulsation pressure (VPP) measurements from upper and lower hemiveins performed by ophthalmodynamometry at least 3 months apart. All subjects had VPP and IOP recorded at two visits, with standard automated perimetry, central corneal thickness (CCT) recorded at the initial visit. Where venous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…This result is reasonable, as the aforementioned changes in pressure will reduce the overall perfusion pressure of the LC. It has also been shown that both an increase in central venous pressure and a decrease in arterial pressure are risk factors for the development of OAG, [49][50][51][52] and our result suggests that changes in blood pressure can significantly impact LC hemodynamics and potentially contribute to OAG progression.…”
Section: Discussionsupporting
confidence: 65%
“…This result is reasonable, as the aforementioned changes in pressure will reduce the overall perfusion pressure of the LC. It has also been shown that both an increase in central venous pressure and a decrease in arterial pressure are risk factors for the development of OAG, [49][50][51][52] and our result suggests that changes in blood pressure can significantly impact LC hemodynamics and potentially contribute to OAG progression.…”
Section: Discussionsupporting
confidence: 65%
“…A couple of studies have been conducted by using the CLD [ 13 , 25 32 ]. The very high concordance correlation coefficient according to Lin of 0.96 makes it possible to compare the results of the mentioned earlier studies with future results obtained by the IOPstim taking into account that the IOPstim values are 1 mm lower than with the CLD method.…”
Section: Discussionmentioning
confidence: 99%